Design and Evaluation of an Experimental Visible Light Communications Platform - Soto-Gomez, J (Institute of Electrical and Electronics Engineers Inc., 2022)
Visible Light Communication (VLC) based systems are proving to be a promising candidate for the development of 6G communication networks. However, new developments in devices and materials need to be done to deal with the limitations and drawbacks of VLC. In the meantime, the work and the experiments done in this paper show that it s possible to implement a light based communication system in non-controlled environments, getting positive SNR values while having several noise and interference sources such as ambient and artificial lightning. All of this within the context of designing and implementing an experimental VLC platform for academic research such as, but not limited to, the implementation of VLC technologies for underground mining facilities. © 2022 IEEE.
Keywords: IEEE 802.15.7; optical wireless communications (OWC); software defined radio (SDR); visible light communication (VLC)